MEMBANGUN SUMBER DAYA MANUSIA SEJAHTERA (Studi Kasus di Provinsi Kalimantan Selatan) - M. Ma’ruf Abdullah (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2009)
The development of human resources is the kry to success of a state in terms of creating people prosperiry and social welfare. This condition can be empirically witnessed in a number of developed countries engaged in OECD (Organization for Economic and Co-operation for Development). In the creating of social prosperiry, a state is certainly faced by various problems, mainly in the sectors related to the improvement of the competitive qualiry of human resources, such as education, healtly, economy, and the power to purchase. The problem of developing human resources should be placed as the main concern of the state. This attempt is aimed at establishing competitive advantage and producing excellent Indeks Pemahaman Manusia (IPM) or Human Development Index (HDI). With excellent and competitive human resources, Indonesia will be able to create social welfare as that hoped by the founder father of the nation.